Use of smart-technologies in the educational process at the department of histology, cytology and embryology of ZDMPhU - Aliyeva, O. G.; Popazova, O. O.; Makeyeva, L. V.; Gromokovska, T. S.; Алієва, Олена Геннадіївна; Попазова, Олена Олександрівна; Макєєва, Людмила Валеріївна; Громоковська, Тетяна Сергіївна (Харків : Міська друкарня, 2023)
The aim of this work: to analyze the experience of using digital technologies in the distance form of the educational process at the Department of Histology, Cytology and Embryology of ZSMPhU.
Aliyeva O. G. - https://orcid.org/0000-0003-1287-674X; Popazova O. O. - https://orcid.org/0000-0001-7740-460X; Makeyeva L. V. - https://orcid.org/0000-0002-3188-2638; Gromokovska T. S. - https://orcid.org/0000-0003-0729-8818.